1997
DOI: 10.1002/(sici)1097-0290(19970620)54:6<503::aid-bit1>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Protein denaturation by combined effect of shear and air-liquid interface

Abstract: The effect of shear alone on the aggregation of recombinant human growth hormone (rhGH) and recombinant human deoxyribonuclease (rhDNase) has been found to be insignificant. This study focused on the synergetic effect of shear and gas‐liquid interface on these two model proteins. Two shearing systems, the concentric‐cylinder shear device (CCSD) and the rotor/stator homogenizer, were used to generate high shear (> 106) in aqueous solutions in the presence of air. High shear in the presence of an air‐liquid inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
3
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(223 citation statements)
references
References 10 publications
13
206
3
1
Order By: Relevance
“…In both experiments, the air-liquid interface was present, yet this interfacial area alone was insufficient to drive aggregation upon milder agitation. We do not dispute the importance of the air-liquid interface in protein instability 32,33 but argue that the main factor determining protein aggregation in our experiments was the concentration of non-native species in solution. The observed disparity between the mild and rigorous agitation experiments can be explained by reversible changes in protein structure.…”
Section: Agitation-induced Mab Aggregationmentioning
confidence: 56%
“…In both experiments, the air-liquid interface was present, yet this interfacial area alone was insufficient to drive aggregation upon milder agitation. We do not dispute the importance of the air-liquid interface in protein instability 32,33 but argue that the main factor determining protein aggregation in our experiments was the concentration of non-native species in solution. The observed disparity between the mild and rigorous agitation experiments can be explained by reversible changes in protein structure.…”
Section: Agitation-induced Mab Aggregationmentioning
confidence: 56%
“…38 Further studies on both samples showed that rhGH denatured upon exposure to high shear in the presence of an air-liquid interface whereas rhDNase remained relatively stable. 64 The stability of rhDNase was attributed to its comparatively high surface tension and low foaming tendency in solution.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
“…Several studies show that the initial destabilization of the protein structure occurs at the solvent-air or solvent-solid interface, where surface tension forces unfold the native protein. 36,37,64,79 The air-water interfacial force is estimated to be 140 pN, 80 taking the air-water interface to be 2 nm in depth with a 0.07 N/m surface tension. 81 This value is comparable to the 150 pN observed to unfold globular proteins in atomic force microscopy studies.…”
Section: Protein Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported for example that shear flows increase protein adsorption [86], which is obviously of interest in the context of the human circulatory system where shear rates can vary from 1 sec -1 to 10 5 sec -1 [90]. However, while protein aggregation has been studied at high shear flow rates (10 6 sec -1 ) [91,92] adsorption to surfaces is yet to be probed under these conditions. Further, it is generally believed that in multi-component systems, smaller proteins adsorb fastest, which are then displaced by larger ones [83,85].…”
Section: Introductionmentioning
confidence: 99%